2017
DOI: 10.1097/j.pain.0000000000001064
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of pain severity in juvenile idiopathic arthritis: results from the Research in Arthritis in Canadian Children Emphasizing Outcomes cohort

Abstract: We studied children enrolled within 90 days of juvenile idiopathic arthritis diagnosis in the Research in Arthritis in Canadian Children Emphasizing Outcomes (ReACCh-Out) prospective inception cohort to identify longitudinal trajectories of pain severity and features that may predict pain trajectory at diagnosis. A total of 1062 participants were followed a median of 24.3 months (interquartile range = 16.0-37.1 months). Latent trajectory analysis of pain severity, measured in a 100-mm visual analogue scale, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
6
25
0
Order By: Relevance
“…Divergent pain trajectories have been shown previously in JIA [810]. Studies describe a consistently low pain trajectory in many patients (≥50%) and a persistently high pain trajectory in 11.1% [8] or 17.9% [9] of patients, lower than reported here (24.2%).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Divergent pain trajectories have been shown previously in JIA [810]. Studies describe a consistently low pain trajectory in many patients (≥50%) and a persistently high pain trajectory in 11.1% [8] or 17.9% [9] of patients, lower than reported here (24.2%).…”
Section: Discussionsupporting
confidence: 62%
“…Recent studies show that only a subset of children with JIA (10–20%) develop persistent pain over 5 years from disease onset [810]. These findings suggest that pain sensitivity may vary in JIA patients and that certain biological and psychosocial factors may contribute to this sensitivity and the development of persistent pain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Lomholt put it: "pain was still a problem for a subgroup of children though they were in remission with biological agents" [17]. In a trajectory analysis, Shiff et al reported that disease activity only accounted for a small portion of variability in pain severity in children with JIA [18]. The same picture emerged for fatigue: although fatigue is a prominent feature in many JIA patients, disease activity seems not to be directly related to it [19][20][21].…”
mentioning
confidence: 99%